2020
DOI: 10.3390/diagnostics10080587
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fecal Calprotectin in Patients with Systemic Sclerosis and Small Intestinal Bacterial Overgrowth (SIBO)

Abstract: Fecal calprotectin (FC) is a quick, cost-effective, and noninvasive test, which is used to diagnose patients with active inflammatory bowel diseases (IBD). Recent studies suggest the possible predictive role of FC in the diagnosis of small intestinal bacterial overgrowth (SIBO) in patients with systemic sclerosis (SSc). This study aimed to assess the predictive value of FC in SSc patients and its’ possible use as a SIBO marker. A total of 40 SSc patients and 39 healthy volunteers were enrolled in the study. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Finding out about micronutrient de ciency which is one of malnutrition symptoms, can be obtained by various laboratory tests (52). In Polkowska-Pruszyńskas's study, FC is a sensitive and speci c indicator for the diagnosis of SIBO in SSc patients, but FC alone is not su cient to diagnose SIBO (53). the Calprotectin level correlated with intestinal wall thickness, the presence of (SIBO), and micronutrients of studied patients.…”
Section: Discussionmentioning
confidence: 91%
“…Finding out about micronutrient de ciency which is one of malnutrition symptoms, can be obtained by various laboratory tests (52). In Polkowska-Pruszyńskas's study, FC is a sensitive and speci c indicator for the diagnosis of SIBO in SSc patients, but FC alone is not su cient to diagnose SIBO (53). the Calprotectin level correlated with intestinal wall thickness, the presence of (SIBO), and micronutrients of studied patients.…”
Section: Discussionmentioning
confidence: 91%
“…Initial biochemical characterization of SIBO patients showed an increase in CRP and FC as compared with controls ( Table 1 ). Fecal calprotectin is frequently considered as a marker of SIBO, especially when this disorder is associated with some mental disturbances, reflecting a potential involvement of the gut–brain axis in SIBO pathogenesis [ 9 ]. In turn, increased CRP as a marker of inflammation, confirms inflammatory aspects of SIBO as it can evoke an inflammatory reaction in the intestinal mucosa, potentiating main symptoms of the disease, although no correlation was found between SIBO severity and inflammation in obese children [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently applied diagnostic tests suffer from serious limitations, as they largely either invasive or unreliable [ 6 , 8 ]. Some authors link SIBO with inflammation and consequently, inflammatory markers, such as fecal calprotectin, can be used to diagnose the disease (reviewed in [ 9 ]). Some nutritional disturbances, including increased folate and vitamin B12 deficiency, resulting from bacterial synthesis of folic acid, can be helpful in SIBO diagnosis ([ 6 ]).…”
Section: Introductionmentioning
confidence: 99%
“…49 Patients with SIBO complain more frequently of abdominal pain/discomfort, bloating, diarrhea or constipation compared to healthy controls (HC). 50 Furthermore, patients with SIBO have higher levels of fecal calprotectin (a bowel inflammatory marker). 50 Approximately 10% of SSc patients can develop malnutrition, 51 with lower levels of serum albumin and vitamin B12 and reduced quality of life.…”
Section: Microbiota Changes In the Lower Digestive Tractmentioning
confidence: 99%
“…50 Furthermore, patients with SIBO have higher levels of fecal calprotectin (a bowel inflammatory marker). 50 Approximately 10% of SSc patients can develop malnutrition, 51 with lower levels of serum albumin and vitamin B12 and reduced quality of life. 49,51 Regarding the microbiota composition in SSc and SIBO patients, a study published in 2019 reported an abundance of Odoribacter, Bilophila and Lachnospira species, finding…”
Section: Microbiota Changes In the Lower Digestive Tractmentioning
confidence: 99%